Bamboo reinforced self-compacting concrete one-way slabs for sustainable construction in rural areas. Issue 1 (1st January 2018) - Adom-Asamoah, Mark; Osei, Jack; Afrifa, Russell
Abstract: The paper presents an experimental study on the structural performance of the combined application of bamboo and self-compacting concrete (SCC) in the construction of reinforced concrete slabs, with the primary aim of helping to maintain a sustainable construction sector, particularly in developing region and rural localities. A total of 12 specimens were cast; six each of a normal concrete (NC) matrix and SCC were subjected to four-point bending test under monotonic action. The major design parameter was the percentage of bamboo reinforcing bars. Two specimens were made to have the same percentage of longitudinal reinforcement, that is, either 1%, 2% or 3%. Results indicated that the post-cracking stiffness of bamboo reinforced SCC slabs is lower than NC slabs. Moreover, varying the percentage of bamboo reinforcement from 1% to 3% in SCC slabs can double the corresponding increase in load and flexural deformation capacities. Finally, in the absence of any blind prediction, and for this limited study, the reliability of available partial factor of safeties for bamboo, should be investigated and reviewed appropriately, since 75% of the anticipated flexural capacity of slabs were utilised experimentally.